Underserved populations at historically black colleges and universities : the pathway to diversity, equity, and inclusion - Davis, Cheron H.; Hilton, Adriel A.; Outten, Donavan L. (Diversity in higher education ;, 2018)
This book focuses on the lived experiences of underserved student and faculty populations at historically Black colleges and universities (HBCUs) and the implications these experiences have for higher education policy. Contributors discuss the contexts and experiences of students and faculty who navigate the political and social spaces of HBCUs while supporting healthy personal and robust professional goals. The stigmas and social nuances that plague students and faculty of color do not dissolve with their arrival at an HBCU, but rather they transform into a new set of challenges that demand the attention of researchers. Taking into account institutional supports, identity development, and socialization patterns, this book sheds light on what the experiences of higher education's "outsiders" mean for future research and practice, while emphasizing issues of diversity, equity, and inclusion.